Vector competence of Culex quinquefasciatus from Santiago Island, Cape Verde, to West Nile Virus: exploring the potential effect of the vector native Wolbachia - Aires Januário Fernandes da Moura; Filipe Tomaz; Tiago Melo; Gonçalo Seixas; Carla A. Sousa; João Pinto (Parasites & Vectors, 2024)
Abstract Background Culex quinquefasciatus plays a crucial role as a vector of West Nile virus (WNV). This mosquito species is widely distributed in Cape Verde, being found in all inhabited islands of the archipelago. However, no data are currently available on the susceptibility of the local mosquito population to WNV. This study aimed to assess the vector competence of Cx. quinquefasciatus mosquitoes from Santiago Island, Cape Verde, for WNV and to explore the potential impact of its native Wolbachia on virus transmission. Methods Wolbachia-infected and uninfected Cx. quinquefasciatus female mosquitoes were exposed to WNV lineage 1 PT6.39 strain using a Hemotek membrane feeding system. Mosquito samples, including the body, legs, wings and saliva, were collected at days 7, 14 and 21 post-infection (dpi) to assess WNV infection through one-step quantitative real-time PCR (RT-qPCR). Results Culex quinquefasciatus from Cape Verde exhibited high susceptibility to the tested strain of WNV. Also, treated females without their native Wolbachia exhibited significantly higher WNV load in their bodies and greater dissemination rate at 7 dpi than their wild-type counterparts carrying Wolbachia. Conclusions The high susceptibility to WNV of Cx. quinquefasciatus from Cape Verde poses a potential risk for virus transmission in the archipelago. However, Wolbachia infection in this mosquito species seems to confer protection against WNV dissemination in the early stages of viral infection. Additional research is required to uncover the mechanisms driving this protection and its potential impact on WNV transmission. Graphical abstract